The temporal cleavage: the case of populist retrotopia vs. climate emergency. Issue 5 (29th July 2022) - Hanusch, Frederic; Meisch, Simon
ABSTRACT: How do time perceptions politicize contestation in the case of climate politics? We argue that across Western Europe and North America, contestation in the climate case and beyond forms along an emerging temporal dividing line. The climate movement's reference to the scientific understanding of climate with its nonnegotiable timescales is at odds with populism's Great Again 'retrotopias' referring to a romanticized fossil fuel past in which climate change is nonexistent. We understand these two distinct temporal positions within society as represented by sometimers and anytimers with each having their very own social structure, collective identity, and organizational manifestation. If supported by further studies, the generalized characteristics of sometimers and anytimers will allow for the development of a substantial temporal cleavage that might be indicative for the Anthropocene.